The Isolation and Spectroscopic Characterization of Products from the Metatheses of Alkyl Oleates - Kamaruddin, Rose aini; Mohammad Nordin, Nor Asyikin; Buang, Nor Aziah (Universiti Putra Malaysia Press, 1994)
The products from the metathesis reactions of methyl and ethyl oleate were isolated using column chromatography. The various components obtained were characterized using infrared (IR), 1Hand 13C nuclear magnetic resonance spectroscopy (NMR) and gas chromatography mass spectrometry (GC-MS)